The Development of the Analytical Thinking Ability Enhancement Model to Enhance Teacher Students, Faculty of Education, Rajabhat Universities through Knowledge Management Learning - Jaruariyanon, Wilawan (Journal of Education Studies, Chulalongkorn University, 2020)
The purposes of this experimental research were to study the analytical thinking of teacher students at Faculty of Education, Rajabhat Universities and create and study the effects of using the analytical thinking Enhancement Model to enhance Teacher Students of Faculty of Education, Rajabhat Universities through Knowledge Management Learning. There were 2 phases of research: Phases I: study the analytical thinking of 320 student teachers. The analytical thinking ability were investigated by the analytical thinking test. Phase II: Create the learning plan to enhance analytical thinking for student teachers. The samples in phase II were students in Chandrakasem Rajabhat University. The experimental plan was The Posttest-only Nonequivalent Control Groups Design. Research tool was an analytical thinking test. Data were analyzed by using percentage, average, standard deviation, and t-test. The research results found that all 3 aspects of analytical thinking ability of student teachers mean scores were below the set criteria (65%) at the 0.01 level of significant. The developed Model consisted of 2 parts: 1) knowledge management learning activities consisted of 4 steps which were identifying the problems, planning, co-creating, and applying knowledge, 2) analytical thinking enhancement activities consisted of 2 steps which were preparing and organizing activities. After the experiment, the average score of analytical thinking abilities of the experimental group was higher than the control group both in overall and separate part which the significant at the 0.01 level.